Prenatal care of women who give birth to Children with Fetal Alcohol Spectrum Disorder in a universal health care system: A retrospective cohort study utilizing linkable administrative data - Singal, Deepa; Brownell, Marni; Wall-Wieler, Elizabeth; Chateau, Dan; Hanlon-Dearman, Ana; Longestaffe, Sally (International Journal of Population Data Science, 2018)
Introduction Fetal Alcohol Spectrum Disorder (FASD) is a significant public health concern. Prenatal care (PNC) settings are integral to preventing prenatal alcohol exposure as physicians delivering PNC services are in a unique position to reduce alcohol consumption during pregnancy. However, few studies have investigated PNC use among women who drink during Objectives and Approach Analysis was conducted of women with children born in Manitoba between April 1, 1984 and Mach 31, 2012, with follow up till 2013 using linkable administrative and novel clinic data. Study group included women whose child(ren) were diagnosed with FASD from 1999 to 2012 (n=702) at a centralised FASD diagnostic clinic. Comparison group included women from the general population whose children who did not have an FASD diagnosis (n=2097), matched on the index child’s birthdate, postal code, and SES. Adequacy of PNC utilization was defined using the revised Graduated Index of Prenatal Care Utilization. Results This is the first population-based study to investigate rates of PNC usage of women who have given birth to children with FASD. Rates of inadequate PNC were higher among the study group (adjusted RR 2.47, 95% CI 2.08 to 2.94), as well as no PNC (adjusted RR 3.55, CI 2.42 to 5.22). Among the study group 63% accessed PNC, with 59% receiving intermediate, adequate, or intensive PNC. Conclusion/Implications Results represent opportunity for screening and brief intervention programs to be delivered in PNC health care settings, as well as outreach programs to facilitate the uptake of PNC among high risk women.